2010
DOI: 10.1159/000288166
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Permeability Barrier Recovery Is Delayed in Vitiligo-Involved Sites

Abstract: Background/Objectives: Prior studies have demonstrated that both the skin surface pH and epidermal permeability barrier function vary with skin pigmentation types. Although melanin deficiency is the main feature of vitiligo, alterations in cutaneous biophysical properties in vitiligo have not yet been well defined. In the present study, stratum corneum (SC) hydration, the skin surface pH and epidermal permeability barrier function in vitiligo were evaluated. Methods: A total of 30 volunteers with vitiligo comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 141 publications
(90 reference statements)
5
41
0
Order By: Relevance
“…Melanin indices of histamine- and vehicle-treated sites, as well as contralateral, uninvolved normal skin sites were measured at baseline using a Mexameter® MX 18 probe connected to a Multiprobe Adapter System (Courage-Khazaka, Cologne, Germany), and again after 5 weeks of treatments [29]. Melanin indices were expressed as percentage of normal skin, calculated according to the equation: (lesion melanin index/contralateral normal skin) × 100.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Melanin indices of histamine- and vehicle-treated sites, as well as contralateral, uninvolved normal skin sites were measured at baseline using a Mexameter® MX 18 probe connected to a Multiprobe Adapter System (Courage-Khazaka, Cologne, Germany), and again after 5 weeks of treatments [29]. Melanin indices were expressed as percentage of normal skin, calculated according to the equation: (lesion melanin index/contralateral normal skin) × 100.…”
Section: Methodsmentioning
confidence: 99%
“…Reduction in lesion size was calculated using the equation: (pretreatment weight - posttreatment weight)/pretreatment × 100. Transepidermal water loss rates, an indicator of epidermal permeability barrier function in lesions, were measured with a TM300 probe, connected to a Courage-Khazaka MPA5 prior to and after 5 weeks of treatments, as described previously [29]. After 5 weeks of treatments, the barrier recovery rate was assessed 3 h after acute barrier perturbation by sequential D-squame applications [29].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When comparing the response of skin affected by vitiligo to contra lateral unaffected skin using tape stripping, Liu et al 44 found that barrier recovery was delayed in vitiligo as measured by transepidermal water loss. This would be a failure of the main function of keratinocytes and supports the view that for vitiligo, we must examine the keratinocyte.…”
Section: Lerner's Theory Of Self-destructionmentioning
confidence: 99%
“…In the present study, TEWL measurements were compared to in vivo laser scanning microscopic measurements (LSM), in order to study the skin barrier function and the structure of the SC [18,19]. Additionally, the skin elasticity and the SC hydration were analyzed.…”
Section: Biophotonicsmentioning
confidence: 99%